Factors Affecting Digital Media Acceptance for Journalistic Purposes: From the Theory of Planned Behavior Perspective - Pasha, Saadia; Sharif, Humaira; Hashmat, Shazia (Journal of Applied Research and Multidisciplinary Studies, 2022)
Digital media has transformed the journalism landscape across the globe. Still, the reasons behind its wider adoption in developing regions are under investigation. This study also examined digital journalism acceptance among Pakistani journalists. The researchers used a cross-sectional approach and used Structural Equation modelling (SEM) for the data analysis. Supported by the basic propositions of the Theory of Planned Behavior, the findings affirmed the role of certain psychological factors in digital media acceptance among journalists. The researchers found that Subjective Norms significantly affect the Behavioral Intention of the journalists, which also indicates a positive effect on Perceived Behavioral Control. Besides, the Perceived Behavioral Control also affects the Behavioral Intention. Consequently, Behavioral Intention causes Digital Journalism Acceptance among journalists. Finally, the indirect effect of gender on Digital Journalism Acceptance also remained significant among Pakistani journalists. This research concluded that the role and acceptance of digital journalism are expanding in Pakistan. Despite the traditional approaches are still considered important, the role of digital journalism is also acknowledged at different levels. Thus, more studies are recommended to explore the role of gender and demographics on digital media acceptance among journalists can bring out in-depth details.